Ultrasound and click chemistry lead to a new chitin chelator. Its Pd(II) complex is a recyclable catalyst for the Sonogashira reaction in water. (15th January 2021) - Kritchenkov, Andreii S.; Kletskov, Alexey V.; Egorov, Anton R.; Kurasova, Margarita N.; Tskhovrebov, Alexander G.; Khrustalev, Victor N.
Highlights: Chitin was used as an accessible and easily-modifiable support for Pd(II)-catalyst. Chitin modification was achieved without a backbone scission or deacetylation. A rare case of an amphiphilic chitin derivative is presented. The derivative allows non-laborious preparation of uniform nanoparticles. Abstract: For the first time the possibility of chitin use as an accessible and easily-modifiable support for an efficient Pd(II) catalyst has been demonstrated. The modification of chitin avoiding a noticeable chain scission or deacetylation, is achieved by sonochemical alkylation with 1-azido-3-chloropropan-2-ol followed by a convenient azido-alkyne click reaction. The obtained polymer represents an extremely rare case of the chitin derivative soluble both in water and organic solvents. The treatment of that derivative with imino-isonitrile Pd(II) complex solution yielded a chitin-supported Pd(II) complex. The latter could be obtained as a powder or as uniform nanoparticles in different size ranges. The nanoparticles with a hydrodynamic diameter of 30 nm were shown to be the most efficient form of catalyst for the copper- and phosphine-free Sonogashira cross-coupling in water.